2017
DOI: 10.1111/dom.12833
|View full text |Cite
|
Sign up to set email alerts
|

Use of incretin agents and risk of acute and chronic pancreatitis: A population‐based cohort study

Abstract: Incretin use was associated with an increased risk of any pancreatitis. Moreover, risk of any and acute pancreatitis was higher when applying a new-user design. We were not able to detect an association with chronic pancreatitis, but the number in this subgroup was small.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 49 publications
(143 reference statements)
1
21
1
Order By: Relevance
“…Our data are in line with the results from a meta‐analysis of randomized studies for vildagliptin, a meta‐analysis for DPP‐4 inhibitors based on observational data only or of both, observational and RCTs and various noninterventional studies which reported no increased risk of acute pancreatitis compared to DPP‐4 inhibitor nonusers. In contrast, a recent noninterventional study and a meta‐analysis of three large randomized DPP‐4 inhibitor outcome trials (none of which included vildagliptin) reported an increased risk of pancreatitis.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Our data are in line with the results from a meta‐analysis of randomized studies for vildagliptin, a meta‐analysis for DPP‐4 inhibitors based on observational data only or of both, observational and RCTs and various noninterventional studies which reported no increased risk of acute pancreatitis compared to DPP‐4 inhibitor nonusers. In contrast, a recent noninterventional study and a meta‐analysis of three large randomized DPP‐4 inhibitor outcome trials (none of which included vildagliptin) reported an increased risk of pancreatitis.…”
Section: Discussionmentioning
confidence: 84%
“…Some of the discrepancies with noninterventional studies may be explained by different study designs, limited sample size and follow‐up and adjustment for confounding factors. Additionally, increased number of pancreatitis cases reported by doctors while prescribing DPP‐4 inhibitors could be due to diagnostic bias as a result of warnings by regulatory agencies on the possible pancreatic adverse events associated with DPP‐4 inhibitors . Nevertheless, based on the currently available data, there is no evidence suggesting that vildagliptin is associated with an increased pancreatitis risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intestinal mucosa permeability will change as the intestinal tract gradually becomes inflammatory, and the mucous membrane permeability will be greatly improved when inflammation is increased [9,10]. Study has shown that some lactic acid bacteria can alleviate DSS-induced colitis by improving the permeability of intestinal mucosa [11]. Clinical studies have also reported that Lactobacillus can significantly assist in the treatment of UC drug therapy [12].…”
Section: Biomedical Research 2018; 29 (4): 768-774mentioning
confidence: 99%
“…Analyses of the FDA Adverse Event Reporting System database and health insurance data have raised concerns about a potential increase in pancreatitis with use of GLP-1RAs based therapies [7,8]. However, recent epidemiological studies have demonstrated GLP-1RAs treatment does not appear to increase the risk of acute pancreatitis in patients with T2DM [9][10][11][12]. Further, obesity and/or T2DM themselves are risk factors for the development of pancreatitis and obesity increases pancreatitis severity and mortality rate [13][14][15].…”
Section: Introductionmentioning
confidence: 99%